Relationship between Chinese middle-aged and old couples' Confucian coping thinking and marital quality - Fan, Zhiguang; Wu, Hanwei; Tao, Min; Chen, Lei (Frontiers in Public Health, 2022)
Objective Drawing on the actor-partner interdependence model (APIM), the present study investigated the relationship between Chinese middle-aged and old couples' Confucian coping thinking and their marital quality in the hope to provide a theoretical basis for ameliorating marital quality. Methods With 744 middle-aged and old couples as participants, the Confucian Coping Questionnaire (CCQ) and the Quality of Marriage Index (QMI) were employed to probe the relationship between responsibility thinking (RT), pro-setback thinking (PT), fate thinking (FT), and marital quality. Results Husbands' and wives' scores in responsibility thinking and pro-setback thinking had significantly positive correlations with their own and their spouses' scores in marital quality, respectively, and husbands' and wives' scores in fate thinking had significantly negative correlations with their own and their spouses' marital quality, respectively. Husbands' responsibility thinking, pro-setback thinking, and fate thinking had a significant actor effect. Husbands' responsibility thinking and fate thinking had a significant partner effect. Wives' responsibility thinking, pro-setback thinking, and fate thinking had a significant actor effect. Wives' responsibility thinking and pro-setback thinking had a significant partner effect. Conclusion From the perspective of dyadic relationships, the present study found that responsibility thinking and pro-setback thinking could positively predict marital quality, while pro-setback thinking could negatively predict marital quality.